Corrigendum: Anti-viral drug discovery against monkeypox and smallpox infection by natural curcumin derivatives: a computational drug design approach - Akash, Shopnil; Hossain, Arafat; Hossain, Md Sarowar; Rahman, Md Mominur; Ahmed, Mohammad Z; Ali, Nemat; Valis, Martin; Kuca, Kamil; Sharma, Rohit (Frontiers in cellular and infection microbiology, 2023)
[This corrects the article DOI: 10.3389/fcimb.2023.1157627.].
Keywords: molecular dynamic simulation; curcumin; admet; DFT; monkeypox; smallpox virus; molecular docking